Reversible MRI lesions after seizures - (:unkn) unknown (W B SAUNDERS CO LTD, 1997)
After generalized or partial seizures, transient lesions may appear on magnetic resonance (MR) images. The mechanisms of MR changes might be a defect in cerebral autoregulation and blood-brain permeability. We report a patient with partial and secondary generalized tonic-clonic seizures. After her first seizure which was generalized tonic-clonic in nature, we detected multiple high signal intensities over the frontal cortical area on proton density images which were enhanced with gadolinium on TI-weighted images. The first and repeated EEGs showed no abnormalities or epileptic discharges. We started carbamezapine (600 mg/d) and excluded systemic diseases like vasculitis, infections, aetiological factors causing cerebrovascular diseases. In the follow-up, she was seizure free under antiepileptic therapy and no other nerological deficit. Repeated MR scans after 24 months from her first seizure revealed no pathologic signal intensities. Although the pathophysiology is unknown, recognition of reversible lesions helps diagnostic and therapeutic approaches to abnormal MR findings after seizures.
Keywords: magnetic resonance imaging; epilepsy; irreversible lesions; partial seizure; PARTIAL STATUS EPILEPTICUS; ABNORMALITIES; EPILEPSY